2019
DOI: 10.1101/819185
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coordination through inhibition: control of stabilizing and updating circuits in spatial orientation working memory

Abstract: 15Spatial orientation plays a crucial role in animal navigation. Recent studies of tethered 16Drosophila melanogaster (fruit fly) in a virtual reality setting showed that the 17 orientation is encoded in the form of an activity bump, i.e. localized neural activity, in 18 the torus-shaped ellipsoid body (EB). Moreover, a fly can maintain working memory of 19 its orientation with a stable and persistent activity bump in the absence of any visual 20 cue, and update the memory in accordance with changes of the bod… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 68 publications
(91 reference statements)
1
3
0
Order By: Relevance
“…They spent more time moving along the edge as evident by the denser distribution of traces in the outer rim area than in the inner circle. This observation is consistent with the common notion of the open-region avoidance behavior of fruit flies, in particular for those without functioning wings [ 9 , 14 ]. This result indicated that the arena did provide a homogeneous illuminating environment without any cue that can elicit directional bias ( Fig 1E–1G ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…They spent more time moving along the edge as evident by the denser distribution of traces in the outer rim area than in the inner circle. This observation is consistent with the common notion of the open-region avoidance behavior of fruit flies, in particular for those without functioning wings [ 9 , 14 ]. This result indicated that the arena did provide a homogeneous illuminating environment without any cue that can elicit directional bias ( Fig 1E–1G ).…”
Section: Resultssupporting
confidence: 92%
“…It is interesting to note that, fruit flies with different genetic backgrounds may perform differently in Buridan’s paradigm. For example, although the white-eyed w 1118 flies are known to have poor vision, in another ongoing study we discovered that this types of flies actually perform decently in an arena that used dimmer green LEDs as the light source [ 14 ]. Therefore, the optimal experiment setup may well depend on the strain of the flies and is worth a systematic study in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, our results confirm that the Drosophila heading direction network contains the core components of a ring attractor while also revealing unpredicted structural features that might enable the heading system to accurately track the animal's heading with a small number of neurons. Importantly, however, these and other models of attractor networks in the fly have assumed the circuit's connectivity based on relatively indirect evidence (Cope et al, 2017;Han et al, 2019;Kakaria and de Bivort, 2017;Kim et al, 2017;Su et al, 2017;Turner-Evans et al, 2017). For example, the location of pre-and post-synaptic arbors has been inferred from whether neural processes visible in light-microscopic images seem spine-or bouton-like in specific substructures (Hanesch et al, 1989;Lin et al, 2013;Wolff et al, 2015).…”
mentioning
confidence: 99%